Prosthetic aortic graft replacement of the ascending thoracic aorta alters biomechanics of the native descending aorta as assessed by transthoracic echocardiography. - Maria C Palumbo; Lisa Q Rong; Jiwon Kim; Pedram Navid; Razia Sultana; Jonathan Butcher; Alberto Redaelli; Mary J Roman; Richard B Devereux; Leonard N Girardi; Mario F L Gaudino; Jonathan W Weinsaft (PLoS ONE, 2020)
Introduction In patients with ascending aortic (AA) aneurysms, prosthetic graft replacement yields benefit but risk for complications in the descending aorta persists. Longitudinal impact of AA grafts on native descending aortic physiology is poorly understood. Methods Transthoracic echocardiograms (echo) in patients undergoing AA elective surgical grafting were analyzed: Descending aortic deformation indices included global circumferential strain (GCS), time to peak (TTP) strain, and fractional area change (FAC). Computed tomography (CT) was used to assess aortic wall thickness and calcification. Results 46 patients undergoing AA grafting were studied; 65% had congenital or genetically-associated AA (30% bicuspid valve, 22% Marfan, 13% other): After grafting (6.4±7.5 months), native descending aortic distension increased, irrespective of whether assessed based on circumferential strain or area-based methods (both p<0.001). Increased distensibility paralleled altered kinetics, as evidenced by decreased time to peak strain (p = 0.01) and increased velocity (p = 0.002). Augmented distensibility and flow velocity occurred despite similar pre- and post-graft blood pressure and medications (all p = NS), and was independent of pre-surgical aortic regurgitation or change in left ventricular stroke volume (both p = NS). Magnitude of change in GCS and FAC was 5-10 fold greater among patients with congenital or genetically associated AA vs. degenerative AA (p<0.001), paralleling larger descending aortic size, greater wall thickness, and higher prevalence of calcific atherosclerotic plaque in the degenerative group (all p<0.05). In multivariate analysis, congenital/genetically associated AA etiology conferred a 4-fold increment in magnitude of augmented native descending aortic strain after proximal grafting (B = 4.19 [CI 1.6, 6.8]; p = 0.002) independent of age and descending aortic size. Conclusions Prosthetic graft replacement of the ascending aorta increases magnitude and rapidity of distal aortic distension. Graft effects are greatest with congenital or genetically associated AA, providing a potential mechanism for increased energy transmission to the native descending aorta and adverse post-surgical aortic remodeling.